Pengaruh Temporal Leadership dan Transformational Leadership terhadap Self-Efficacy dan Psychological Empowerment pada Karyawan Swasta Generasi Z di DKI Jakarta - Qorry Rahma Intan Palupi; Netania Emilisa; Adellia Adellia (Jurnal Syntax Admiration, 2024)
The purpose of this study is to analyze Temporal Leadership, Transformational Leadership, Self-Efficacy, and Psychological Empowerment, as well as to examine the influence of Temporal Leadership and Transformational Leadership on Self-Efficacy, the influence of Self-Efficacy on Psychological Empowerment, and the influence of Temporal Leadership and Transformational Leadership on Psychological Empowerment. The design of this study was carried out by means of hypothesis testing which was used to test the influence of Temporal Leadership and Transformational Leadership on Self-Efficacy and Psychological Empowerment in Generation Z Private Employees in DKI Jakarta. As a result, this study concluded that Generation Z private employees in DKI Jakarta felt the existence of Temporal Leadership and Transformational Leadership in their companies, which affected their Self-Efficacy and Psychological Empowerment. Statistical descriptions show that employees feel comfortable with Temporal Leadership because convenience is the main factor in decision-making, and Transformational Leadership increases confidence, enthusiasm, and creativity at work.